The deubiquitinase Leon/USP5 interacts with Atg1/ULK1 and antagonizes autophagy. - Pai, Y.L.; Lin, Y.J.; Peng, W.H.; Huang, L.T.; Chou, H.Y.; Wang, C.H.; Chien, C.T.; Chen, G.C. (Cell death & disease, 2023)
Accumulating evidence has shown that the quality of proteins must be tightly monitored and controlled to maintain cellular proteostasis. Misfolded proteins and protein aggregates are targeted for degradation through the ubiquitin proteasome (UPS) and autophagy-lysosome systems. The ubiquitination and deubiquitinating enzymes (DUBs) have been reported to play pivotal roles in the regulation of the UPS system. However, the function of DUBs in the regulation of autophagy remain to be elucidated. In this study, we found that knockdown of Leon/USP5 caused a marked increase in the formation of autophagosomes and autophagic flux under well-fed conditions. Genetic analysis revealed that overexpression of Leon suppressed Atg1-induced cell death in Drosophila. Immunoblotting assays further showed a strong interaction between Leon/USP5 and the autophagy initiating kinase Atg1/ULK1. Depletion of Leon/USP5 led to increased levels of Atg1/ULK1. Our findings indicate that Leon/USP5 is an autophagic DUB that interacts with Atg1/ULK1, negatively regulating the autophagic process.